Determining Crystallite Size Using Scherrer Formula, Williamson-Hull Plot, and Particle Size with SEM - Sumadiyasa, Made; Manuaba, I.B.S. (BULETIN FISIKA; Vol 19 No 1 (2018): BULETIN FISIKA, 2018)
It has been determined the crystallite size by XRD technique using Scherrer equation and Williamson-Hull Plot method. While the particle size is determined by SEM using Image-J software. For this purpose, synthesized samples of compound Gd 0,95 La 0.05 Ba 2 Cu 3 O 7- d phase. From the calculation results, obtained the crystallite size in nanometers order, however the crystallite size resulting from the Scherrer equations and Scherrer Modified is different, i.e. 63.1675 nm and 67.0005 nm.  The results of the crystallite size calculation by the scherrer equation directly and modified differed from that of the Williamson-Hull Plot method (97,3040 nm). Meanwhile, the results of the Williamson-Hull Plot methods and SEM show almost the same value (98.7297 nm) .